4a+b-5a-3b=0

Simple and best practice solution for 4a+b-5a-3b=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4a+b-5a-3b=0 equation:


Simplifying
4a + b + -5a + -3b = 0

Reorder the terms:
4a + -5a + b + -3b = 0

Combine like terms: 4a + -5a = -1a
-1a + b + -3b = 0

Combine like terms: b + -3b = -2b
-1a + -2b = 0

Solving
-1a + -2b = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '2b' to each side of the equation.
-1a + -2b + 2b = 0 + 2b

Combine like terms: -2b + 2b = 0
-1a + 0 = 0 + 2b
-1a = 0 + 2b
Remove the zero:
-1a = 2b

Divide each side by '-1'.
a = -2b

Simplifying
a = -2b

See similar equations:

| 100-25x[-10]= | | 6+5x^2=13x | | (2x-9)/(x-5) | | (3x-3)=(5x+15) | | (5x+15)=(3x-3) | | X-(5x-1/3)=8-(6/5) | | -2x+y=a | | 5x+7x-12=144 | | 7x^2+31x-38=0 | | x^2+x-0.01=0 | | 7x^2+3x+3x+4=-3x+5 | | 2x/-3x=2 | | 4x^2-2x=px^2+2x+3 | | 7x=8x-15 | | 6x-3=10x+5 | | (2x^2-7x+3)(2x^2-x+3)+8x^2=0 | | 5x=40+3 | | -16=-5+2(2-m) | | 2x=19/6 | | 204=2y+y | | 5(x+3)+x=4(x+5)+3 | | 2x+80-4x=50 | | x(x/3)=12 | | x(x/3) | | x*x/3 | | 9x+2(60)=7x+7(60) | | c=120+.65y | | (2a-3)(4a^2+6a+9)=0 | | 2y+5y(2-y)=3-5y | | x(3x)=8 | | x^2-6x+y=0 | | x^3-4x^2+5x+2=0 |

Equations solver categories